Peran Pemerintah Daerah Dalam Pengembangan UMKM Pengolahan Waluh Sebagai Produk Unggulan Di Kabupaten Semarang - ruben angga saputra; puji astuti; wiwik widayati (Journal of Politic and Government Studies, 2015)
AbstractOne of the things that can be favored by the Semarang District is processed foods made from pumpkin. Although now there are SMEs that can process the pumpkin into other foods such as geplak, chips, Gelek, pumpkin seeds, egg roll and others, SME development also requires rule of Local Government, especially the Department of Cooperatives, SMEs, Trade and Industry in order to develop properly, either through partnerships, funding and even promotion. So that the production of this pumpkin processing SMEs into Regional Competitive Products (PUD) District Semarang. The method used in this study is a qualitative stud. The result shows that the role of the Semarang District Government through the Department of Cooperatives, SMEs, Trade and Industry has been good enough in implementing development through existing programs although in some sectors not yet optimal.